(untitled) (Research, Society and Development, 2024)
Madness has a history shaped by different eras and cultural boundaries. This can be seen in the literature on the subject, particularly in Michel Foucault 1961 work, History of Madness. The social representation of madness has been shaped by cultural, religious, political, and philosophical factors. With the advent of mental health in modernity, a concept that stands in opposition to the social representation of madness emerged. But what impact did this work have on studies that conceptualize mental health and illness? Focusing on this question, the present study offers a literature review. The timeframe spans from 1962 to the present day. The objective is to establish some benchmarks regarding how Foucault redefined perspectives on madness and mental health, and to assess how scholars perceive the relationship between his ideas and previous views.